Modernity versus Tribal Identity: A Study of the Misings of Lakhimpur District of Assam: The Impact of Modern Development on the Misings of Lakhimpur District, Assam (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Known as a riverine tribe of Assam, the Misings of Assam basically dwell on the flood plains of the rivers originating in the sub Himalayan hills of Arunachal Pradesh. They have been historically associated with pisciculture, wet rice cultivation, animal husbandry and collecting forest produces for survival. In fact, as the very term ‘tribe’ indicates, the Misings dwell in locales away from the centres of trade, commerce and political powers. However, modern developmental projects of the state and central governments have started reaching most of the people and they are fast integrating with the other developed societies. This paper studies the Mising people living in a few villages in the district of Lakhimpur experiencing the gains of development albeit in a slow pace and they appear to be enthusiastically welcoming modernity as a means of social, economic and cultural development.